Bernard Pelletier - Jaime Wisniak (Revista CENIC Ciencias Químicas, 2017)
Bernard Pelletier (1761-1797) a pharmacist and physician, devoted his short life to the application of chemistry to practical problems of industry and national activity in France. Among them we can mention the behavior of deliquescent salts, phosphorus and its derivatives, graphite and molybdenite, platinum, copper, chlorine, gunpowder, soap, and ethers.